Interpersonal Meaning in B.J. Habibie’s Speech: A Systemic Functional Analysis of Mood and Modality - Mar' Atul Latifah Jauharin Nafi' (Universitas Negeri Semarang, 2026)
Language functions as a medium of communication but also as a tool for establishing social roles and relationships. This study explores the construction of interpersonal meaning in a political speech delivered by B.J. Habibie, the third President of Indonesia, through the lens of Systemic Functional Linguistics (SFL). The research specifically investigates how mood and modality are employed to enact interpersonal functions. The objectives of this study are threefold: (1) to identify the types of mood and modality used in the speech, (2) to determine the dominant mood and modality, and (3) to analyze how interpersonal meaning is constructed through their use. This qualitative study employed document-based content analysis using Halliday and Matthiessen’s (2004) framework. The data consisted of a transcript of Habibie’s “Indonesian Historical Evolution,” speech delivered at the Carnegie Endowment for International Peace. Clauses were analyzed for grammatical mood types, declarative, interrogative, imperative, and degrees of modality: low, medium, and high. The findings indicate that declarative mood (82.4%) and low-degree modality (47%) dominate the speech, suggesting a rhetorical strategy to inform and engage the audience respectfully, rather than commanding. The use of high-modality expressions like “have to” signals moments of urgency and persuasion. These patterns reflect the speaker’s intent to maintain authority while fostering inclusivity and national reflection. The study concludes that mood and modality play a pivotal role in shaping the interpersonal dynamics of political discourse. It recommends further cross-cultural investigations to examine how political figures employ interpersonal strategies in global communication contexts.